Teachers’ well-being beyond perceived stress: Exploring the relative contribution of emotional intelligence facets to Spanish teachers’ happiness - Mérida-López, Sergio; Quintana-Orts, Cirenia Luz; Rey-Peña, Lourdes; Extremera-Pacheco, Natalio (My University, 2022)
Background Emotional intelligence (EI) is a personal resource typically linked to higher well-being in human service professionals. However, it is unknown which EI facets are more predictive in explaining different indicators of well-being beyond that accounted for by other key predictors such as perceived stress. Aims This study investigated the specific role of different EI facets in explaining happiness above perceived stress among teaching professionals. Method A total of 1323 Spanish teachers (821 female) from educational centers located in southern Spain took part in this study. Results Main results showed that self-emotion appraisal, use of emotions and regulation of emotions contributed to the prediction of teachers‘ happiness beyond the effects of sociodemographic variables and perceived stress. Conclusion Self-focused EI dimensions involving appeared to be the most important predictors of happiness even controlling for stress experienced by teachers. These findings support the empirical utility of specific EI facets and indicate that its predictive power for teachers´ happiness is not simply attributable to overlap with measures of stress-related constructs.
Keywords: Profesores; Teachers; Stress; Happiness; Emotional intelligence; Inteligencia emocional